2022
DOI: 10.3389/fenvs.2022.1027323
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based assessment of selective heavy metals and stable carbon isotopes in groundwater of Islamabad and Rawalpindi, Pakistan

Abstract: This study applied a nuclear technique in conjunction with a classical monitoring tool to characterize the origin, fate, and behavior of metal pollutants in groundwater of Islamabad-Rawalpindi Metropolitans, which are also known as the “twin cities.” In total, 122 groundwater samples were collected and analyzed in accordance with standard methods. GIS and multivariate statistical analysis were employed for the groundwater vulnerability assessment and source apportionment. The results of the aesthetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…From the results of the physicochemical evaluation, arsenic (As) and lead (Pb) were the most potent contaminants in the study region. Our multielement analysis results for Cu, Mg, Pb, Ni, Mn and Na align with the findings of Rana et al (2022). However, unlike their research, which found arsenic (As) levels within permissible limits, our study detected higher concentrations of arsenic.…”
Section: Resultssupporting
confidence: 85%
“…From the results of the physicochemical evaluation, arsenic (As) and lead (Pb) were the most potent contaminants in the study region. Our multielement analysis results for Cu, Mg, Pb, Ni, Mn and Na align with the findings of Rana et al (2022). However, unlike their research, which found arsenic (As) levels within permissible limits, our study detected higher concentrations of arsenic.…”
Section: Resultssupporting
confidence: 85%